The Role Of Green Accounting In Promoting Corporate Sustainability - Salma Dewi Ambarsari; Salva Dewi Ambarwati; Hwihanus Hwihanus (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Through literature analysis, this study identifies various concepts, methods and practices related to Green Accounting. This concept includes carbon footprint measurement, product life cycle analysis, environmental impact evaluation and sustainability reporting. Methods such as input-output analysis, environmental cost analysis, and ecological value evaluation are used to measure and account for the environmental impact of a company's activities. The research results show that implementing Green Accounting can help companies identify opportunities for resource efficiency, reduce environmental risks, improve the company's image, and meet stakeholder demands regarding sustainability. However, challenges such as limited data, measurement complexity, and lack of uniform standards are still obstacles in implementing Green Accounting. The global perspective in this study highlights differences in the acceptance and implementation of Green Accounting in various countries and industrial sectors. Several developed countries have adopted regulations that encourage sustainability reporting, while developing countries still face challenges in integrating Green Accounting principles into their business practices. Thus, this research concludes that Green Accounting has an important role in encouraging corporate sustainability globally. Further research is needed to overcome implementation challenges and increase understanding of the positive impacts that can be generated through implementing Green Accounting in the context of corporate sustainability.